Terrorism, Radicalisation, Extremism, Authoritarianism and Fundamentalism: A Systematic Review of the Quality and Psychometric Properties of Assessments. - Akimi Scarcella; Ruairi Page; Vivek Furtado (PLoS ONE)
Background Currently, terrorism and suicide bombing are global psychosocial processes that attracts a growing number of psychological and psychiatric contributions to enhance practical counter-terrorism measures. The present study is a systematic review that explores the methodological quality reporting and the psychometric soundness of the instruments developed to identify risk factors of terrorism, extremism, radicalisation, authoritarianism and fundamentalism. Method A systematic search strategy was established to identify instruments and studies developed to screen individuals at risk of committing extremist or terrorist offences using 20 different databases across the fields of law, medicine, psychology, sociology and politics. Information extracted was consolidated into two different tables and a 26-item checklist, reporting respectively background information, the psychometric properties of each tool, and the methodological quality markers of these tools. 37 articles met our criteria, which included a total of 4 instruments to be used operationally by professionals, 17 tools developed as research measures, and 9 inventories that have not been generated from a study. Results Just over half of the methodological quality markers required for a transparent methodological description of the instruments were reported. The amount of reported psychological properties was even fewer, with only a third of them available across the different studies. The category presenting the least satisfactory results was that containing the 4 instruments to be used operationally by professionals, which can be explained by the fact that half of them refrained from publishing the major part of their findings and relevant guidelines. Conclusions A great number of flaws have been identified through this systematic review. The authors encourage future researchers to be more thorough, comprehensive and transparent in their methodology. They also recommend the creation of a multi-disciplinary joint working group in order to best tackle this growing contemporary problem.